INOVASI PUPUK ORGANIK CAIR DARI ALERINE (AIR KELAPA, AIR LERI, DAN URINE) SEBAGAI UPAYA MENINGKATKAN PERTUMBUHAN TANAMAN - Samodra Widad Prima Pratama; Ryan Putra Hidayat; Dewi Nirmala Sari; Alvin Rahadiansyah Afandi; Denny Oktavina Radianto (KOLONI, 2023)
The use of chemical fertilizers is no stranger to Indonesian farmers. Directly, chemical fertilizers have polluted the environment. Initially, chemical fertilizers were able to increase crop yields but over time yields declined and soil conditions became more critical. Chemical fertilizers can kill organisms in the soil. This is because chemical fertilizers contain compounds such as methane and ammonia which pollute the environment. Thus, innovation is needed by utilizing leri water, coconut water and urine as liquid organic fertilizer. The aim of this research is to find out the process of making and the feasibility of the material into liquid organic fertilizer. Based on the results obtained from this experiment, leri water, coconut water and urine can be processed into liquid fertilizer by mixing 2.5 liters of urine, 100 milliliters of EM-4, 0.5 liters of water, 2 liters of leri water, 1 liter of water coconut, and 100 grams of brown sugar then ferment it for 14 days. This process aims to remove the odor from the urine. Liquid Organic Fertilizer from Alerine is ready to be applied to chili and rice plants, showing an increase in growth compared to liquid fertilizers on the market. Production costs of only IDR 3,500 can produce 6 liters of Liquid Organic Fertilizer from Alerine. Tests on soil and worms that were carried out for 1 week showed that the soil that was given chemical fertilizers tended to be harder. In addition, the number of worms in it decreased compared to the soil that was given Alerine Liquid Organic Fertilizer. This is because the content of Liquid Organic Fertilizer from Alerine is Nitrogen, Potassium, Activated Carbon, growth regulators, and other complex compounds. Suggestions for further research should use more drops to ferment fertilizer. The author hopes that farmers will make Liquid Organic Fertilizer from Alerine which is environmentally friendly as a substitute for chemical fertilizers. Keywords: Coconut Water, Leri Water, Urine, Liquid Organic Fertilizer